A cross-country psychiatric screening of ICD-11 disorders specifically associated with stress in Kenya, Nigeria and Ghana. Issue 1 (31st December 2020) - Ben-Ezra, Menachem; Hyland, Philip; Karatzias, Thanos; Maercker, Andreas; Hamama-Raz, Yaira; Lavenda, Osnat; Mahat-Shamir, Michal; Shevlin, Mark
ABSTRACT: Background : The Global Forum for Health Research, with the support of the World Health Organization, highlighted the need to prioritize mental health research in Africa. The introduction of revised descriptions of Posttraumatic Stress Disorder (PTSD) and Adjustment Disorder, along with new diagnoses of Complex PTSD and Prolonged Grief Disorder, in the ICD-11 creates a need for additional national-level epidemiological studies on the prevalence of stress-related disorders. Methods : The prevalence rates of these four ICD-11 stress disorders were assessed in three African countries including Nigeria (N = 1006), Kenya (N = 1018), and Ghana (N = 500). Participants completed disorder-specific measures for each disorder. Findings : Across the entire sample, the current prevalence rate of probable Adjustment Disorder was 8.4% (95% C.I. = 7.4%, 9.6%), probable PTSD was 18.6% (95% C.I. = 17.2, 20.2%), probable Complex PTSD was 15.9% (95% C.I. = 14.5%, 17.4%) and probable Prolonged Grief Disorder was 3.7% (95% C.I. = 3.1%, 4.5%). Interpretation : The results are applicable primarily to well-educated urban and suburban adults in these African countries. Results indicated that Adjustment Disorder, PTSD, and CPTSD are highly prevalent in these three African countries. There is now a pressing need to develop culturally sensitive interventions to enable recovery from these conditions.